Intercostal Nerve Cryoanalgesia in Pectus Excavatum Repair – A Narrative Review - Marguła, Robert Rudolf; Szostawicki, Michał; Figiel, Aniela; Zaborek, Paweł; Bernad, Mateusz; Widomska, Katarzyna; Pestka, Justyna (Quality in Sport, 2026)
Background. Effective postoperative pain management is a major challenge after minimally invasive pectus excavatum repair. Cryoanalgesia has developed as a potential support to conventional analgesic strategies. This narrative review summarizes current evidence for the efficacy of intercostal nerve cryoanalgesia after Nuss procedure in pediatric population with pectus excavatum. Aim. The aim of this narrative review was to sum up current evidence comparing intercostal nerve cryoanalgesia with conventional analgesic strategies following surgical repair of pectus excavatum in pediatric population. Material and methods. A narrative literature review was performed using PubMed and Cochrane databases. Studies evaluating intercostal nerve cryoanalgesia in pediatric patients undergoing the Nuss procedure were analyzed, with particular focus on length of hospital stay, procedure duration, pain outcomes, and opioid consumption. Results. Cryoanalgesia was associated with a shorter hospital stay compared to conventional analgesic strategies and longer time of procedure. Pain outcomes and opioid usage varied across studies. Conclusions. Cryoanalgesia appears to be a promising adjunct to postoperative pain management strategies for patients undergoing minimally invasive repair of pectus excavatum. Across the reviewed studies, the cryoanalgesia was associated with shorter hospital stay and longer procedural time compared to standard analgesic strategies. Pain outcomes and opioid usage varied across studies, but available evidence suggests that cryoanalgesia of intercostal nerves may reduce postoperative opioid usage and improve postoperative pain control. Further high-quality randomized trials are necessary to evaluate the optimal cryoanalgesia protocol.